1991
DOI: 10.1037/0278-7393.17.5.897
|View full text |Cite
|
Sign up to set email alerts
|

Memory for things forgotten.

Abstract: As previous research has shown, items not recalled on an initial memory task are not simply forgotten. Often, some can be recalled on a later, second task. Further, subjects can generally predict, in terms of feeling-of-knowing (FOK) ratings, which items will be subsequently recalled. Two experiments were carried out to assess both second-task performance and FOK accuracy for unrecalled items as a function of two factors, encoding manipulations (levels of processing in Experiment 1, study time in Experiment 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 46 publications
9
42
1
1
Order By: Relevance
“…In word memory, it has been repeatedly shown that subjects who study words semantically (e.g., by judging the pleasantness of each word) have better recall performance than those who study the words perceptually (e.g., by judging the number of vowels contained in each word). This LOP effect on word recall is highly robust and contrasts with its lack of(or weak) influence on (implicit) word stem completion (Graf & Mandler, 1984;Graf, Mandler, & Haden, 1982;Java & Gardiner, 1991;Light & Singh, 1987;Lupker, Harbuk, & Patrick, 1991;Micco & Masson, 1991;Nelson, Shreiber, & Holley, 1992;Park & Shaw, 1992;Roediger, Weldon, Stadler, & Riegler, 1992;Schacter & Church, 1992;Squire, Shimarnura, & Graf, 1987). One important divergence with word memory is that changes in timbre attributes did not influence the (implicit) affect judgments but did so for (explicit) recognition of the melodies.…”
Section: Discussionmentioning
confidence: 99%
“…In word memory, it has been repeatedly shown that subjects who study words semantically (e.g., by judging the pleasantness of each word) have better recall performance than those who study the words perceptually (e.g., by judging the number of vowels contained in each word). This LOP effect on word recall is highly robust and contrasts with its lack of(or weak) influence on (implicit) word stem completion (Graf & Mandler, 1984;Graf, Mandler, & Haden, 1982;Java & Gardiner, 1991;Light & Singh, 1987;Lupker, Harbuk, & Patrick, 1991;Micco & Masson, 1991;Nelson, Shreiber, & Holley, 1992;Park & Shaw, 1992;Roediger, Weldon, Stadler, & Riegler, 1992;Schacter & Church, 1992;Squire, Shimarnura, & Graf, 1987). One important divergence with word memory is that changes in timbre attributes did not influence the (implicit) affect judgments but did so for (explicit) recognition of the melodies.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy for feeling of knowing tends to be higher (1) for general-information questions than for paired-associate learning , (2) for items studied to a higher criterion than for those studied to a lower criterion (Nelson et al, 1982), (3) for items with more alternatives at test than for those with fewer (Schwartz & Metcalfe, 1994), and (4) for items with a wider range of difficulty than for those with a narrower range (Nelson, Leonesio, Landwehr, & Narens, 1986;Schwartz & Metcalfe, 1994). Feeling of knowing also predicts performance in n-alternative recognition (Blake, 1973;Hart, 1967a), yes/no recognition (Costermans et aI., 1992), first-letter cued recall (Gruneberg & Monks, 1974), reminiscence (Metcalfe et aI., 1993), stem completion (Lupker et al, 1991), and perceptual identification and relearning (Nelson et aI., 1984). Although most amnesic patients do show accurate feeling of knowing, patients with Korsakoff's amnesia cannot predict performance (Shimamura & Squire, 1986).…”
Section: Feeling-of-knowing Judgmentsmentioning
confidence: 99%
“…Since Hart's seminal work, much research has focused on feeling of knowing, and other researchers have extended Hart's RJR technique (see Metcalfe & Shimamura, 1994;Nelson, 1992). Indeed, many researchers have used ordinal or magnitude scales to assess feeling of knowing (Blake, 1973;Nelson et al, 1982;Nelson & Narens, 1980a;Schacter, 1983;Wellman, 1977) and have substituted other criterion tests for recognition, such as reminiscence (Gruneberg & Sykes, 1978;Hart, 1967b;Metcalfe et aI., 1993), first-letter cued recall (Gruneberg & Monks, 1974), lexical decision (Connor, Balota, & Neely, 1992;Yaniv & D. E. Meyer, 1987), stem completion (Lupker, Harbluk, & Patrick, 1991), perceptual identification (Nelson et al, 1984), relearning (Nelson et al, 1984), and attribute identification (Koriat, 1993;Schacter & Worling, 1985).…”
Section: Feeling-of-knowing Judgmentsmentioning
confidence: 99%
“…If they were, then manipulations that influence either cue familiarity or target retrievability would have no effect. Much data show that such variables do influence judgments (Blake, 1973;Koriat & Lieblich, 1977;Lupker et al, 1991;T. Nelson et al, 1982;Reder, 1987;Reder & Ritter, 1992;Schwartz & Metcalfe, 1992).…”
mentioning
confidence: 99%